The survey on "Family Models in Germany" (FAMOD): A description of the data - Anja Steinbach; Sven A. Brocker; Lara Augustijn (Universität Duisburg-Essen, Institut für Soziologie, 2020)
The FAMOD project, which is funded by the German Research Foundation (DFG), investigates the diversity of existing family Models after separation or divorce in Germany. The project's aim is to provide detailed information about the living conditions of mothers, fathers, and children in different post-separation family configurations, namely in sole physical custody (SPC) and in joint physical custody (JPC) arrangements. Employing a multi-actor design, the survey closely examines the well-being of the Individual family members in order to identify the potentials and challenges within a specific physical custody care arrangement. Because JPC families are still extremely rare in Germany (less than 1% of all families with minor children), this project is the first to collect data from a sufficient number of JPC families for detailed statistical analyses. Based on a quota sample, FAMOD provides data of 1,554 families in Germany (nuclear, SPC, and JPC families). This working paper contains a description of the sampling procedure, details about the process of data collection, and a benchmarking of selected core sociodemographic variables against the results from other German surveys.
Keywords: 300; data quality; FAMOD; joint physical custody; sampling; sole physical custody